Interactive Sonification: Aesthetics, Functionality and Performance. - Weinberg, Gil; Thatcher, Travis (Leonardo Music Journal, 2006)
The authors present a sonification installation that allows a group of players to interact with an auditory display of neural activity. The system is designed to represent electrical spike propagation in a neuron culture through sound propagation in space. Participants can simulate neural spikes by using a set of specially designed controllers, experimenting and sonically investigating the electrical activity of the brain. The article discusses some aesthetic and functional aspects of sonification and describes the authors' approach for group interaction with auditory displays. It concludes with the description of a performance piece for the system and ideas for improvements and future work.